2018
DOI: 10.1038/s41422-018-0044-4
|View full text |Cite
|
Sign up to set email alerts
|

MAP3K1 and MAP2K4 mutations are associated with sensitivity to MEK inhibitors in multiple cancer models

Abstract: Activation of the mitogen-activated protein kinase (MAPK) pathway is frequent in cancer. Drug development efforts have been focused on kinases in this pathway, most notably on RAF and MEK. We show here that MEK inhibition activates JNK-JUN signaling through suppression of DUSP4, leading to activation of HER Receptor Tyrosine Kinases. This stimulates the MAPK pathway in the presence of drug, thereby blunting the effect of MEK inhibition. Cancers that have lost MAP3K1 or MAP2K4 fail to activate JNK-JUN. Conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 43 publications
6
84
0
1
Order By: Relevance
“…PTCH1 inactivation is frequently observed in basal cell carcinomas. 26 20 All tumor samples obtained from patient OC87 contained p.T405M mutation in the IDH2 gene, which was accompanied by 1p/19q co-deletion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTCH1 inactivation is frequently observed in basal cell carcinomas. 26 20 All tumor samples obtained from patient OC87 contained p.T405M mutation in the IDH2 gene, which was accompanied by 1p/19q co-deletion.…”
Section: Resultsmentioning
confidence: 99%
“…25 OC58 contained p.S288P mutation in the kinase domain of MAP2K4 gene; the inhibitors of this molecule are available in laboratory setting. 26…”
Section: Resultsmentioning
confidence: 99%
“…7,8 An analysis of the treatment responses of PDXs established from 92 patients with different solid tumors demonstrated a significant association between drug response in patients and the response in mice bearing the corresponding PDXs, indicating that PDXs can predict clinical treatment response. 4 PDX models also are increasingly used in the mechanistic characterization of resistance to targeted therapies, [9][10][11] the identification of novel Cancer November 1, 2019 biomarkers 12 and therapeutic targets, 13 and the characterization of intratumoral heterogeneity. 14,15 Molecular characterization of lung cancer PDXs has demonstrated that these PDXs faithfully retain the genomic alterations found in their corresponding primary tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Most clinical studies with MEK inhibitors have yielded disappointing results, due at least in part to the paucity of biomarkers of MEK inhibitor sensitivity and toxicity. Bernards and co‐workers recently showed data suggesting that cancers having mutations in MEK4 or its upstream kinase MEKK1, which are frequent in tumors of breast, prostate and colon, may respond to MEK inhibitors . Their findings also suggest that MEKK1 and MEK4 are potential drug targets in combination with current MEK inhibitors, in spite of the fact that they are encoded by putative tumor suppressor genes.…”
Section: Figurementioning
confidence: 99%